2014
DOI: 10.1080/19393210.2014.968880
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in yogurt samples

Abstract: The concentrations and distributions of major polycyclic aromatic hydrocarbons (PAHs) were determined in 20 kinds of yogurt specimens collected from Italian supermarkets using reversed phase high-performance liquid chromatography equipped with fluorescence detection. The method was validated by determination of recovery percentages, precision (repeatability) and sensitivity (limits of detection) with yogurt samples fortified at 0.25, 0.5 and 1 µg/kg concentration levels. The recovery of 13 PAHs, with the excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Polycyclic aromatic hydrocarbons are toxic compounds having a low solubility in water and constitute a large class of organic compounds, containing 2 or more fused aromatic rings composed of carbon and hydrogen atoms (EFSA (European Food Safety Authority), 2008 ; SCF (Scientific Committee on Food), 2002 ). They are produced from incomplete combustion of the organic matter when foods such as fish or meat are processed by smoking, grilling, or roasting (Battisti et al., 2015 ; EFSA (European Food Safety Authority), 2008 ; Ingenbleek et al., 2019 ; Yusuf et al., 2015 ). Several studies reported that fat dropping in the flame during grilling processing contributes to PAHs formation (Chen et al., 2013 ; Viegas, Novo, Pinto, et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons are toxic compounds having a low solubility in water and constitute a large class of organic compounds, containing 2 or more fused aromatic rings composed of carbon and hydrogen atoms (EFSA (European Food Safety Authority), 2008 ; SCF (Scientific Committee on Food), 2002 ). They are produced from incomplete combustion of the organic matter when foods such as fish or meat are processed by smoking, grilling, or roasting (Battisti et al., 2015 ; EFSA (European Food Safety Authority), 2008 ; Ingenbleek et al., 2019 ; Yusuf et al., 2015 ). Several studies reported that fat dropping in the flame during grilling processing contributes to PAHs formation (Chen et al., 2013 ; Viegas, Novo, Pinto, et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAHs with a high molecular mass, such as Indeno (1,2,3-cd) pyrene and benzo(ghi)perylene, were found in only four of the extracted samples (1 M, 3 M, 11 M and 14 M) (yogurt and unsmoked cheese) under investigation at concentrations of 0.012-0.048 µg/g. Battisti et al studied the PAH distribution in yogurt and found that there was an absence of high molecular weight PAHs with the exception of BaP, BaA and CHR in some samples at the concentrations of 0.3, 0.2 and 0.22 µg/g, respectively [22]. A previous study conducted by Guillén et al also assessed the presence of BbF, BkF and IPY in non-smoked cheese [23].…”
Section: Resultsmentioning
confidence: 99%
“…The PAH concentration in samples had a direct relation to fat content of samples, and a higher level PAHs was detected in the high‐fat yoghurt (Battisti et al . ). Furthermore, it was stated that the presence of Bifidobacterium bifidum reduced the level of PAHs detected in the samples.…”
Section: Formation Occurrence and Health Impacts Of Pahs In Milk Andmentioning
confidence: 97%